“Choosing the Best Modality for Undergraduate Clinical Training” A Mixed Method Approach (Medical Forum Monthly, 2024)
Objective: To compare the effectiveness of clinical skills training of undergraduate students who have undergone three different modalities of training consisting of real patients, mannequins/simulations and combination of both by summative assessment.Study Design: Descriptive and comparative studyPlace and Duration of Study: This study was conducted at Foundation University Medical College Islamabad for eight months.Materials and Methods: The study was conducted on undergraduate medical students during gastrointestinal tract (GIT) and Renal modules in year two. Clinical skills techniques of 100 students were examined during an objective structured clinical examination (OSCE). The examination was carried out using real patients, simulated/mannequins and combination of both techniques on Group A (batch 2011), Group B (batch 2012) and Group C (batch 2013) respectively. Total number of stations was ten and examiner rated students independently on clinical skill techniques.Results: Descriptive and comparative statistics for student scores were compiled from the OSCE forms used at the stations. Measures of central tendency, mean and standard deviation were calculated for ten OSCE stations as well as an overall score. Inter-rater reliability between student scores ranged from 0.84-0.89 for the different modalities. There was a significant difference in the performance of group A (real Patients) and group B (Simulated patients) from group C (mixed technique) at all stations and p value 0.05 was considered significant .Conclusion: Significant improvement was noted in the clinical skill techniques of undergraduate students who were trained through mixed method approach as compared to the individual methods.